Parental perspectives on ECEC settings that foster child well-being: A comparison across nine European countries - van Trijp, C. P. J. (2022)
Parents play a vital role in identifying children’s needs for support and Early Childhood Education and Care (ECEC ) features that support children’s well -being.This study examined parental perspectives on features of ECEC that foster young children’s well -being under and above the age of 3 years by interviewing 359 parents across nine European countries (England, Finland, Germany, Greece, Italy, the Netherlands, Norway, Poland, and Portugal). Results revealed that parental perspectives largely converged with quality features discussed in ECEC research. Process quality features were mentioned more frequently than structural features for all children 0- to 6-years-old in almost all countries. However, care -oriented features were mentioned more frequently for under 3 years, and educational-oriented features were mentioned more frequently for the older group. Regarding structural features, patterns of responses across the two age groups were similar in most countries. Age differences were not more pronounced in countries with a split governance system.